Powassan Virus Neuropathology and Genomic Diversity in Patients With Fatal Encephalitis - Normandin, Erica (Open Forum Infect Dis, 2020)
BACKGROUND: Powassan virus (POWV) is an emerging cause of severe encephalitis; very little is known about human pathogenicity due to challenges in diagnosis and viral RNA recovery. We present 3 patients with fatal encephalitis due to POWV lineage II (deer tick virus). METHODS: We obtained 27 unique samples, including from brain biopsy and autopsy, and used metagenomic sequencing, quantitative reverse transcriptase polymerase chain reaction, and a newly developed CRISPR-based diagnostic assay to perform the first detailed characterization of POWV compartmentalization and genomics between and within human subjects. RESULTS: In all 3 patients, imaging and histopathology findings were notable for profound cerebellar involvement. All patients were initially diagnosed with POWV by metagenomic sequencing, and 2 of the 3 had negative clinical testing by serology. We detected POWV RNA in 13 clinical samples; levels were highest in the cerebellum, and there was very little involvement of peripheral tissue. We assembled complete POWV genomes from 8 samples, providing unique information about the strains of POWV lineage II (deer tick virus) that infect humans. CONCLUSIONS: We demonstrate the utility of molecular assays for detecting POWV infection, including in seronegative patients, and nominate viral genomic features that may relate to human infection and neuropathogenicity. The cerebellum was identified as a key target POWV in fatal infection, by radiological and histopathological findings as well as molecular testing.